The effect of vitamin D deficiency on platelet parameters in patients with COVID-19 - Talebzadeh, Amirhossein; Ghaffari, Hadi; Ghaffari, Kazem; Yazdanpanah, Sorur; Yousefi Goltappeh, Bahman; Eslami, Majid; Ghasemi, Ali (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Since there is very little information about the relationship between platelet parameters and vitamin D concentration in patients with COVID-19, the aim of this study is to investigate the relationship between serum vitamin D level and platelet parameters in patients with COVID-19 and to compare these parameters in patients with COVID-19 without vitamin D deficiency and, subsequently, the prognostic value of these parameters in cases of vitamin D deficiency. Methods Seven hundred and forty-three patients diagnosed with COVID-19 were enrolled in this study. Patients were divided into two groups: those with and without vitamin D deficiency. The associations between platelet indices and vitamin D levels were analyzed by Pearson’s correlation analysis and a one-way ANOVA test. Results Platelet count and mean platelet volume (MPV) were significantly higher in the patients with vitamin D deficiency than in the patients without vitamin D deficiency. There was a significant negative correlation between platelet count and MPV with vitamin D levels in patients with vitamin D deficiency (r = -0.835, P = 0.001 & r = -0.324, P = 0.042, respectively). Vitamin D levels in COVID-19 patients can determine the platelet count and MPV of the patients. Discussion The aforementioned results imply that maintaining an elevated concentration of vitamin D in COVID-19 patients is important because it is associated with a decrease in MPV, which in turn reduces susceptibility to diseases such as coronary artery disease.